INFLUENCE OF CIGARETTE SMOKING ON SEMINAL PLASMA SOLUBLE FAS AS A MARKER OF GERM CELL APOPTOSIS (Iraqi Journal of Medical Sciences, 2016)
Background:Male infertility constitutes about 50% of overall causes of infertility and apoptosis is known to have an essential role in the control of germ cell number in testis. Cigarette smoking is common in males at reproductive age. Studying the influence of smoking on apoptosis in male genital tract and its influence on fertility helps in the management of infertility in smokers.Objectives:To assess the influence of cigarette smoking on seminal plasma (SP) soluble Fas (sFas) and the correlation between SP sFas and serum sex steroidal hormones and conventional semen parameters in males of infertile couples.Methods:Seventy male partners of infertile couples (30 smokers and 40 non-smokers) were enrolled in this study. A subject was considered smoker if he had history of smoking of more 10 cigarettes per day for at least one year. Semen analysis was done according to World Health Organization (WHO) 2010. Specific kits were used for the measurement of SP sFas and serum testosterone and estradiol (E2).Results:In smokers' group, SP sFas was significantly (p